Sex differences in the skeletal muscle response to metformin treatment and the possible association with gut-muscle axis in rats - Song, Lin; Wang, Rui; Cui, Jiaqi; Hu, Shuyuan; Wang, Jingyue; Xie, Jiaming; Miao, Pudan; Sun, Bo (Frontiers in Endocrinology, 2025)
IntroductionMetformin (MT) is widely used in treating type 2 diabetes, and muscle is one of the targets for MT action. Recent studies have shown that gut microbiota plays a key role in mediating the clinical effects of MT, as well as affects muscle function, through the gut-muscle axis. However, it is not clear whether the use of MT in non-diabetic population affects muscle metabolism via gut-muscle axis and whether there are sex differences.MethodsWe investigated the effects of ten days MT administration (200 mg/kg/d) on metabolic phenotype, skeletal muscle morphology and function-related gene expression, gut microbiota composition, gut integrity and inflammation, and plasma short chain fatty acids (SCFAs) levels in adult male and female Sprague-Dawley rats.ResultsWe found MT treatment decreased body weight, blood glucose and muscle gene expression involved in myogenesis and mitochondrial biogenesis and dynamics more significant in females, while increased the colonic mRNA expression of more inflammatory markers in males. MT treatment also induced sex-specific alterations in the gut microbiota composition, plasma SCFAs contents and muscle SCFA receptors’ mRNA expression in non-diabetic rats.ConclusionsOur research provides evidence that the use of MT in daily health maintenance may have sex-specific effects on gut-muscle axis and should be approached with caution.